ДИСЛИПИДЕМИЯ И АССОЦИИРОВАНЫЕ МЕТАБОЛИЧЕСКИЕ ЗАБОЛЕВАНИЯ - О. Ш. Ойноткинова; Е. И. Дедов (Архивъ внутренней медицины)
This article presents the pathogenesis of dyslipidemia and associated metabolic disorders with the position of lipid metabolism. The role of natural mechanism of cholesterol homeostasis changing was showed, functional disorders of the enterohepatic circulation of bile acids and intrahepatic cholestasis due to violation of the reticuloendothelial system, entailing disruption of a specific target organ, on the one hand, and the development of atherosclerosis with ischemic syndromes — on the other, were demonstrated. Diagnostic and treatment algorithm is presented.